Local political participation of people in local Traditional conservation in warinchamrap Municipality ubon ratchathani province - phabhangkaro, Paphangkorn; PhrakruPrayutsaratham (Journal of Humanities and Social Sciences Mahamakut Buddhist University Isan Campus, 2023)
The objectives of this thematic paper were as follows: 1) To study the level of local political participation of the people in preserving local tradition in Warin Chamrap municipality Ubon Ratchathani Province 2) to compare people’s participation in local politics in preserving local tradition in Warin Chamrap municipality Ubon Ratchathani province classified by gender, age, education level and occupation. 3) The suggestion of people’s participation in local politics in preserving local tradition in Warin Chamrap municipality, Ubon Ratchathani. The study found that Overall public opinion towards local political participation of the people in preserving local customs in Warin Chamrap municipality Ubon Ratchathani Province at a high level in every aspect. The comparison of public opinions classified by personal factors found that gender, age, education level and occupation were significantly different at the 0.05 level, and to suggest participation in preserving local traditions found people have opinions to disseminate knowledge about local traditions with strategies to make more people join the community and to give importance to the preparation of local development plans by allocating budgets to support community projects And should survey satisfaction in preserving local traditions in terms of public utilities.